If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 + -3 = 2x + 1 Reorder the terms: 4 + -3 + 2x = 2x + 1 Combine like terms: 4 + -3 = 1 1 + 2x = 2x + 1 Reorder the terms: 1 + 2x = 1 + 2x Add '-1' to each side of the equation. 1 + -1 + 2x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 0 + 2x = 1 + -1 + 2x 2x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 2x = 0 + 2x 2x = 2x Add '-2x' to each side of the equation. 2x + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 8h-3-5h-4= | | 0.25(y+2)-0.15(y+3)=4 | | (-7)y+8+15y-14= | | 45x^3-5x+0=0 | | 10x^2-16+6=0 | | [4-(2-4(2-4)+6)]+3=-9 | | 0=-4+x^2 | | 0=4+x*x | | 0=4+x^2 | | x=4+x^2 | | 4m-12=m-6 | | P=11P | | 11-a=2a-6 | | Y-5=4(x-1) | | -1.8(1.03n+0.9)=2.2(2.58n+1.4)-1.4 | | 4.75=a+1.85 | | 1.30m=6.50 | | 6.50=m-1.30 | | 6.50=M+1.30 | | 2a+b=24 | | 2a+3b-a+4a= | | y=65x | | 3a+5a+a= | | (x^4+y^2)dx-(xy)dy=0 | | 14-(6-3r)=4r-r | | y=6y-8y | | 6x-3=x+7 | | 2m+15=8 | | W(a)=2afindw(3) | | H(a)=a^3findh(2) | | -3+2v-1+4=v-3 | | -4n+3n=-15+n+4+5 |